Identification of the Sex Pheromone of the Citrus Leafminer (Phyllocnistis citrella Stainton, Lepidoptera：Gracillariidae) with a Trial of Control by the Communication Disruption Method - Shaban Ali MAFI; Le Van YANG; Yoshihisa NAKATA; Nobuo OHBAYASHI; Masanobu YAMAMOTO; Tetsu ANDO (Journal of Pesticide Science, 2005)
GC-EAD and GC-MS analyses of a pheromone gland extract from virgin females of the citrus leafminer (CLM, Phyllocnistis citrella Stainton) confirmed that the male attractant previously found by random screening tests in a field, (7Z,11Z)-7,11-hexadecadienal (Z7,Z11-16：Ald), is a real pheromone component of CLM. While a field test of lures mixed with extra compounds structurally related to Z7,Z11-16：Ald did not inform candidates for a minor component having a synergistic effect, some compounds, particularly monoenyl derivatives, strongly inhibited the activity of the dienyl pheromone component. Furthermore, two experiments were carried out in citrus orchards to develop a method for disrupting the mating of CLM. In order to estimate the disruptive ability of Z7,Z11-16：Ald and some derivatives, pheromone traps surrounded with septa impregnated with these test compounds were used. However, this first trial was fruitless because the number of captured males actually increased due to the effect of the surrounding compounds such as Z7,Z11-16：Ald. On the other hand, another experiment with polyethylene dispensers containing Z7,Z11-16：Ald revealed a good ability to disrupt the male's orientation, although CLM eggs and larvae on a citrus tender flush did not show any significant difference in the control and treated fields. Monitoring traps caught 27-127 males in one night in control fields from July to September, but hardly any males were caught in either field treated with the dispensers at a density of 500 or 1300 tubes/ha.